Population pharmacokinetics for the CTLA‐4 modulator gotistobart in patients with advanced solid tumors - Tianhong Li; Jiahui Xue; Yang Liu; Jun Yang; Ido D. Weiss; Hasan Abu Kharma; Juanjuan Su; Yuye Shen; Tairan Yang; Kumpal Madrasi; Frank Engler; Shuang Liang; et al. (The Journal of Clinical Pharmacology, 2026)
Abstract Gotistobart is an investigational, next‐generation, humanized IgG1 monoclonal antibody targeting cytotoxic T‐lymphocyte antigen‐4. It is engineered to preserve cytotoxic T‐lymphocyte antigen‐4 through endosomal recycling while enhancing intratumoral regulatory T‐cell depletion. A population pharmacokinetic model was developed to characterize gotistobart pharmacokinetics and identify covariates contributing to inter‐individual variability in patients with advanced solid tumors. Serum concentration‐time data were obtained from 632 patients enrolled in three phase I–III clinical trials. In total, 3406 pharmacokinetic observations across a dose range from 0.1 to 10 mg/kg were collected. A two‐compartment model with linear elimination best described the data, with inter‐individual variability on clearance, central volume, and peripheral volume. Parameter estimates were precise, with typical values of 0.005 L/h for clearance, 0.021 L/h for inter‐compartmental clearance, 2.59 L for central volume, and 3.43 L for peripheral volume. Covariates identified in the model included body weight and albumin on clearance and volumes, and sex on volumes, with limited clinically relevant impact. The model was evaluated using parameter precision, goodness‐of‐fit diagnostics, and prediction‐corrected visual predictive checks. The model was used to simulate concentration‐time profiles for clinically relevant dosing regimens. Simulations demonstrated the expected steady‐state pharmacokinetic behavior, with dose‐dependent increases in peak and trough concentrations. Compared with 6 mg/kg every 3 weeks, administration of two 10 mg/kg loading doses followed by 6 mg/kg every 3 weeks accelerated the attainment of steady state. The validated population pharmacokinetic model provides a quantitative foundation for subsequent exposure‐response analyses and regimen selection.